Ligninolytic Activity of Ganoderma strains on Different Carbon Sources - TYPUK ARTININGSIH (Biodiversitas Journal of Biological Diversity, 2006)
Lignin is a phenylpropanoid polymers with only few carbon bonds might be hydrolized. Due to its complexity, lignin is particularly difficult to decompose. Ganoderma is one of white rot fungi capable of lignin degradation. The ligninolytic of several species Ganoderma growing under different carbon sources was studied under controlled conditions which P. chrysosporium was used as standard comparison. Three types of ligninolytic, namely LiP, MnP, and laccase were assessed quantitatively and qualitatively. Ratio between clear zone and diameter of fungal colony was used for measuring specific activity qualitatively. Four sspecies of Ganoderma showed positive ligninolytic qualitatively that G. lucidum KT2-32 gave the highest ligninolytic. Activity of LiP and MnP in different carbon sources was consistently resulted by G. lucidum KT2-32, while the highest activity of laccase was shown by G. ochrolaccatum SA2-14. Medium of Indulin AT affected production of protein extracellular and induced ligninolytic. Glucose, BMC, and pine sawdust did not affect the activity of ligninolytic. The specific activity of Ganoderma species was found to be higher than the one of P. chrysosporium.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: ligninolytic, Ganoderma, carbon sources